Ultrasound Differential Diagnosis of Various Forms of Acute Pancreatitis - Georg R. Jelena, Alger M. Harrison (Academic Journal of Clinicians, 2023)
Acute pancreatitis is a common disease and ranks third among acute surgical diseases of the abdominal organs, second only to acute appendicitis and acute cholecystitis.Mortality in acute pancreatitis is high, reaching 40% in destructive forms which is largely due to the difficulty of timely diagnosis. Many authors report high mortality rates of 30% or more with necrotizing pancreatitis. Early diagnosis of severe pancreatitis is erroneous in 30-40% of cases. There are no unambiguous clinical and laboratory criteria to differentiate between a local (limited) process and a widespread, aseptic and infected nature of the lesion. This is often the main reason for unjustified delay in surgical intervention, or, on the contrary, expanded indications for surgical intervention, which contributes to the development of severe postoperative complications. The choice of the correct treatment tactics for patients with acute pancreatitis is possible with early diagnosis of this disease with determination of its form and the depth of developing destructive changes in the pancreas, in the tissues surrounding the organ and retroperitoneal tissue. To diagnose acute pancreatitis, various methods are used: laboratory, X-ray, computed tomography, magnetic resonance imaging, angiography, laparoscopy, and ultrasound. The ultrasound method is non-invasive, has no contraindications, can be repeated many times, which provides dynamic control. It allows to assess the condition of the pancreas and tissue of the retroperitoneal space, the biliary system, the condition of parenchymal organs, and the presence of free fluid in the serous cavities. With the use of Doppler ultrasound, it became possible to study the blood supply to the pancreas, which is important for assessing hemodynamic disorders in the organ during the development of pancreatic necrosis. The aim of this work is to improve the diagnosis of various forms of acute pancreatitis.